A Sensitive Amperometric Biosensor Based on Carbon Dot 3-Chloropropyl-trimethoxysilane Modified Electrode for Detection of Neurotransmitter Dopamine. Issue 3 (1st March 2023) - Akbıyık, Muhammed Ali; Bodur, Onur Can; Keskin, Merve; Kara, Meryem; Dinç, Saliha; Arslan, Halit; Özmen, Mustafa; Arslan, Fatma
Abstract : Dopamine (DA) is an important electroactive neurotransmitter. The concentration of DA in the body of a healthy person is approximately 1.0 × 10 −7 −1.0 × 10 −3 M. A decrease in dopamine concentration is associated with Parkinson's disease. Thus, it is important to determine the amount of dopamine in early diagnosis of Parkinson's disease. Different methods such as immunoassay, flow injection analysis (FIA), high performance liquid chromatography (HPLC) etc could be used for determination of dopamine but they are expensive and have long determination times, and pre analytic processes. In this study, a tyrosinase based amperometric biosensor was developed with carbon paste electrode modified with carbon nano dot 3-Chloropropyl-trimethoxysilane (CDs-CPTMS) for determination of the amount of dopamine. CDs-CPTMS was synthesized for the first time. Determination of dopamine was carried out by the reduction of dopamine-o-quinone at −0.15 V versus Ag/AgCl. The effect of temperature, pH, and substrate concentration on the dopamine response of the prepared biosensor and interference effect were investigated. There was no interference effect of uric acid and ascorbic acid. The designed biosensor has wide working range (0.001–0.01 μ M and 0.01−0.1 μ M), low limit of detection, very good reproducibility and shelf life. In addition, the preparation of the biosensor is practical and cost-effective.